Dysregulation of lipid metabolism induced by airway exposure to polycyclic aromatic hydrocarbons in C57BL/6 mice. (February 2019) - Li, Fang; Xiang, Binbin; Jin, Yan; Li, Chao; Li, Jingguang; Ren, Songlei; Huang, Huiting; Luo, Qian
Abstract: Polycyclic aromatic hydrocarbons (PAHs), originated from cigarette smoke and fine particle matter (PM2.5), are important inducers of lung cancer. Lipid metabolic disorder is an important biological feature in the progression of lung cancer. However, the dysregulation of lipid metabolism induced by airway exposure to PAHs remains unknown. In this study, an untargeted lipidomics approach was performed to characterize the effects of airway exposure to benzo[a]pyrene (BaP) on lipid metabolism of C57BL/6 mice. Lipidome of serum samples were analyzed with an ultra-performance liquid chromatography coupled with quadrupole-orbitrap mass spectrometer. Lipid profiling and multivariate statistical analysis results demonstrated that airway exposure to BaP mainly disturbed glycerophospholipid metabolism of mice. Moreover, sex-dependent and time-dependent effects of BaP exposure on lipids profile of mice were observed. Several phosphatidylcholines (PCs), Lysophosphatidylcholines (LysoPCs), phosphatidylethanolamines (PEs), Lysophosphatidylethanolamines (LysoPEs) and phosphatidylinositols (PIs) were significantly down-regulated in mice serum after BaP exposure. Meanwhile, these altered lipids showed different susceptibility and change trends in male and female mice. Our results are corresponding with the lipid metabolic alterations induced by cigarette smoke and PM2.5 in animals or human. Compared with the dysregulation of lipid metabolism in patients with lung cancer, these results indicated that the lipid metabolism response to PAHs airway exposure may contribute to the lung cancer progression. Graphical abstract: Highlights: Effect of airway exposure to PAHs on lipid metabolism was evaluated in C57BL/6 mice. Airway exposure to BaP mainly perturbed glycerophospholipid metabolism of mice. BaP exposure down-regulated the serum levels of PCs, LysoPCs, PEs, LysoPEs and PIs. BaP exposure dysregulated lipid metabolism in a sex- and time-dependent manner. Mechanism of PAHs induced lung cancer on the altered lipid metabolism was proposed. Abstract : PAHs-induced dysregulation of lipid metabolism in C57BL/6 mice with decreasing PCs, LysoPCs, PEs, LysoPEs and PIs levels, might play an important role in the lung cancer progression.